Environmental Informatics: Potentialities in iSchools and Information Science & Technology Programs— An Analysis - P. K. Paul; Ricardo Saavedra; P. S. Aithal; Bashiru Aremu; Pappachan Baby, (International Journal of Management, Technology and Social Sciences (IJMTS), 2020)
Environment is an alarming concern and valuable to all of us, as all of us belong to the environment and ecology in a different context. There are different studies available related to the environment and as far as Informatics is concerned, it is the field of practice and study related to the information systems and information activities using tools, techniques and technologies. The applications of Informatics in different areas and branches are important concerns viz. agriculture, healthcare, transport and tourism, education and training, government and administration, business and commerce; and in this context Environmental Informatics are important. This is the application of Informatics and Information Technologies in the environment and allied subjects. There are universities and academic bodies offering Environmental Informatics academic programs mainly from the environment and allied departments and units. Though, the field is a combination of both the areas and thus can be offered in Informatics or allied departments or bodies. As far as Informatics related branches are concerned important are IT, Information Systems, Information Management, Computer Sciences, etc. And in all these departments or units Environmental Informatics can be started as a Major or Specialization with proper educational policies. iSchools is an international consortium and body dedicated to combining all information related institutes, departments and programs under one roof with a focus on technologies for the societies and different sectors. Thus, the field of Environmental Informatics can be started easily in the iSchools. Furthermore, in recent past iSchools considered as the academic units offering information or IT related programs irrespective of their affiliation to the iSchools Organization, United States. This is maybe considered as a policy paper for the environmentalist, educationalist, IT educators to think about the potentialities of Environmental Informatics in Informatics or IT or simply iSchools related departments, programs, etc.